(untitled) (One Health & Risk Management, 2023)
Introduction. Poverty and disability form a vicious cycle, each reinforcing the other. While there is a widespread acknowledgment of this correlation, the existing evidence supporting and describing this potential association is insufficient. However, there is a need for more studies to explore how low income influences the decline in health-related quality of life and lifestyle among vulnerable people with special needs. This work aims to systematize studies related to the health of people with disabilities, with a particular focus on the situation in low and middle-income countries (LMIC). Aim. The secondary study aims to describe the determinants of health-related quality of life among people with special needs and individuals aged 60 years and older in low- and middle-income countries. Material and methods. Materials and research assessing the relationship between disability, economic poverty, and population aging were searched in ten electronic databases, including PubMed, MEDLINE, EMBASE, Hinari, and Google Scholar. Results. The systematic review revealed robust evidence supporting a strong link between disability and economic poverty. When disaggregated by disability/impairment type, 122 out of 150 (81%) studies reported a statistically significant positive relationship between these two variables. This broad and comprehensive analysis provides solid empirical support for the theoretical arguments regarding the connection between disability and economic poverty. When considering other factors, the majority of the studies included both rural and urban areas (n=83). Studies limited to either rural or urban environments exhibited some differences in their findings on the relationship between disability and poverty. In total, 35 studies included in this review assessed the relationship between disability and employment. Regarding the association between disability and employment status, 26 (74%) found a positive association. This implies that disability was significantly more common among unemployed groups compared to employed groups, or people with disabilities were significantly more likely to be unemployed compared to people without disabilities. Conclusions. While this systematic review has provided clear evidence of a link between disability and economic poverty, further research is needed to understand what Marmot refers to as the "causes of causes": the underlying social, political, and economic conditions that contribute to the connection between disability and economic poverty. Factors such as access to health (including rehabilitation), education, and employment may elucidate part of the relationship between disability and economic poverty, potentially operating in both directions. Although this analysis noted that people with disabilities were more likely not to work, the employment status was a secondary measure with no specific search terms. The observed association, along with other potential factors such as access to health and education, deserves further attention in separate systematic reviews. A deeper understanding of how specific determinants influence the relationship between disability and economic poverty can aid in identifying effective and appropriate interventions and strategies to break the cycle. Note: The study is conducted within the framework of the JPIAMR projects "Phage treatment and wetland technology as intervention strategy to prevent dissemination of antibiotic resistance in surface waters" (PhageLand), project number - 22.80013.8007.1